ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI NILAI TUKAR DOLLAR AMERIKA SERIKAT DI INDONESIA - Wijaya, I Nyoman Agus; Purwanti, Putu Ayu Pramitha (E-Jurnal Ekonomi Pembangunan Universitas Udayana, 2021)
The movement of the rupiah value can affect the stability of the economy in Indonesia. The aim this research ; (1) identify the simultaneous and partial effects of foreign debt, interest rates, foreign direct investment and macro shocks on the US dollar exchange rate in Indonesia; (2) identify among the foreign debt, interest rates, foreign direct investment, and macro shocks that most dominantly affect the US dollar exchange rate in Indonesia. Types and sources data using quantitative approach with secondary data and using multiple linear analysis techniques. The results showed that; 1) foreign debt, interest rates, foreign direct investment, and macro shocks simultaneously had effect on the US dollar exchange rate in Indonesia; 2) foreign debt and macro shocks have positive and significant effect on the US dollar exchange rate in Indonesia, interest rates don’t have significant effect on the US dollar exchange rate in Indonesia, while foreign direct investment has negative and significant effect on the US dollar exchange rate in Indonesia; 3) the dominant variable that affects the US dollar exchange rate in Indonesia is foreign debt, as seen from the standardized coeffiients beta.   Keywords: US Dollar Exchange Rate, External Debt, Interest Rates, Foreign Direct Investment, Macro Shocks.